2011
DOI: 10.1021/om200822e
|View full text |Cite
|
Sign up to set email alerts
|

Benzonitrile Adducts of Terminal Diarylphosphido Complexes: Preparative Sources of “Ru═PR2

Abstract: Dehydrohalogenation of secondary diarylphosphine ruthenium complexes in the presence of benzonitrile yields stable, isolable nitrile adducts of the formula [Ru(η 5indenyl)(PAr 2 )(NCPh)(PPh 3 )], in which the terminal phosphido ligand is pyramidal at P and contains a stereochemically active lone pair. Unlike the analogous carbonyl adducts [Ru(η 5 -indenyl)(PAr 2 )(CO)(PPh 3 )], these benzonitrile complexes behave as masked sources of the highly reactive planar phosphido complexes [Ru(η 5 -indenyl)(PAr 2 )(PPh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
(17 reference statements)
3
26
0
Order By: Relevance
“…donors) to leave a hydride ligand on the metal center has been extensively studied in recent years (Scheme 1). 7 …”
Section: Introductionmentioning
confidence: 99%
“…donors) to leave a hydride ligand on the metal center has been extensively studied in recent years (Scheme 1). 7 …”
Section: Introductionmentioning
confidence: 99%
“…Both stoichiometric and catalytic reactions involving the addition of s bonds across metal-element bonds (element = N, O, C, B, S) have become increasingly prevalent. [25][26][27][28][29][30][31][32] In av ery recent paper by Gudat and coworkers,ametal phosphenium complex, (uNHP Dipp )Mn(CO) 4 (where NHP R indicates amonodentate NHP + cation with N-Rs ubstituents," u" indicates an unsaturated backbone,a nd Dipp = 2,6-diisopropylphenyl), was shown to be an active catalyst for the catalytic dehydrogenation of NH 3 BH 3 . [21][22][23][24] Related examples of metalligand cooperativity involving phosphorus are far less common.…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32] In av ery recent paper by Gudat and coworkers,ametal phosphenium complex, (uNHP Dipp )Mn(CO) 4 (where NHP R indicates amonodentate NHP + cation with N-Rs ubstituents," u" indicates an unsaturated backbone,a nd Dipp = 2,6-diisopropylphenyl), was shown to be an active catalyst for the catalytic dehydrogenation of NH 3 BH 3 . [28][29][30][31][32] Extension of the metal-ligand cooperativity observed for amide/amine systems to phosphide/phosphines poses as ignificant challenge,b ut may result in more reactive systems since P À H bonds are generally weaker and more acidic than N À Hbonds, and because metal phosphides are more nucleophilic than their metal amide congeners. [33] In fact, there are only af ew examples of H 2 addition across aM ÀPb ond.…”
mentioning
confidence: 99%
“…The Rosenberg and Peters groups have both shown that phosphidos are able to deprotonate and orthometalate a phenyl substituent of a cisphosphine ligand on coordinatively unsaturated ruthenium(II) complexes. 17,28,36 This, followed by deprotonation of the resulting phosphine and reductive elimination of the alkyl and phosphido functionalities, could form the 1,2-diphosphinobenzene linkage. In order to reduce the unsaturated backbone from the dppen ligand, on the other hand, the hydrogen atoms would need to come from the activated Cp* methyl group and the aromatic o-C−H bond.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…Despite the metal−phosphorus double bond, planar phosphidos have reactivity similar to that of terminal phosphidos in that they are very basic and nucleophilic; they have even been reported to deprotonate phenyl groups. 17,28,36 Phosphido ligands are especially important in the latetransition-metal-catalyzed hydrophosphination of unsaturated substrates, as conventional organometallic catalytic mechanisms involve the insertion of an alkene or alkyne into the M−P bond of a phosphido intermediate. 22−26,37−59 A typical organometallic mechanism for alkene hydrophosphination involves oxidative addition of a primary or secondary phosphine to an electron-rich metal center followed by coordination of the olefin substrate and subsequent insertion to form a P−C bond (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%